Correlation between body weight and intestinal villi morphology in finishing pigs - Itza Ortiz, Mateo Fabian (2019)
The villi height of the villi is associated with the nutrients’ absorption and greater body weight. The correlation between body weight and villi height or villi area in three sections of the small intestine was investigated. A total of 42 pigs were randomly sampled with an average of 73.61 kg ± 10.72 kg laughtered weight. Three methodologies were used for sampling in each of the three sections of the small intestine. The height and area of the villi were measured for each section of the intestine. Linear Pearson correlations were calculated. The correlations of the height and area of the villi of the ileum were positive and low (r = 0.168; n = 42; p = 0.05). The duodenum and jejunum correlations were negative and low (r = -0.140; n = 42; p > 0.01). No correlation was found between the body weight and the height or area of the villi, possibly due to other factors that may affect them.